Pendekatan Historis-Sosiologis dalam Studi Teks Hadis: A Historical-Sociological Approach to the Study of Hadith Texts - Nuni Nuraini; Dadah Saadah (Institut Daarul Qur'an Jakarta, Indonesia, 2026)
Understanding hadith cannot be separated from the historical context in which it emerged. This study discusses the importance of the historical approach in hadith studies by highlighting the distinction between textual and contextual interpretations, as well as its development from classical traditions to modern thought. In classical scholarship, the concept of asbāb al-wurūd was introduced to explain the circumstances behind hadith emergence, which was later developed systematically by contemporary thinkers such as Fazlur Rahman and Abdul Mustaqim. This study aims to analyze the role of the historical approach in maintaining the relevance of hadith in contemporary contexts. It employs a descriptive qualitative method through a literature review of classical and modern scholarly sources. The findings reveal that applying the historical approach to hadiths on war, jihad, and women demonstrates their contextual nature and orientation toward universal benefit. Therefore, the historical approach not only strengthens textual understanding but also offers a more comprehensive and relevant interpretation for modern society.